Exploring the Real-time Fitness Effects of Tai Chi Exercise: A Test Experiment using a Biophysical Energy Detection Device based on Five Elements Theory - Wang, Yulin; Liu, Xiaolei; Shen, Yutong Shen; Cao, Tingting (The Journal of the International Society of Chinese Health Practices, 2024)
See PDF for details